Comparative Study of Crude Palm Oil Exports to The Main Producing Countries in Asean - Reyhan, Felix; Saputera, Denny (Golden Ratio of Social Science and Education, 2025)
This study aims to analyze and compare the export performance of Crude Palm Oil (CPO) from Indonesia, Malaysia, and Thailand, as the leading producers in ASEAN, from 2014 to 2023. This research uses a descriptive quantitative approach to evaluate production, consumption, export volume, export value, and competitiveness through the Market Share Index (MSI) indicator. The results indicate that Indonesia dominates the global CPO market, with the highest average export volume and export value compared to Malaysia and Thailand. Domestic policies, such as export restrictions, and global market dynamics influence Indonesia's export value fluctuations. Malaysia demonstrates stable production and domestic consumption but faces challenges in enhancing its international competitiveness. As the smallest producer, Thailand shows steady growth but contributes significantly less than the other two countries. Factors such as government policies, changes in global prices, and extreme weather conditions affect the export performance of all three countries. This study is expected to provide strategic insights for improving the competitiveness of CPO exports in the international market.